The impact of digital economy development on subjective well-being: micro-level evidence from China - Li, Hao; Li, Jiao; Yang, Zihan (Frontiers in Public Health, 2025)
IntroductionIn the era of digital transformation, exploring the welfare implications of societal changes and in particular the relationship between digital economy development and subjective well-being (SWB) has emerged as a critical focus of academic research. Clarifying how digital economy development affects SWB and its underlying mechanisms is essential for improving societal welfare and quality of life in the context of digitalization.MethodsThis study employs empirical analysis to address the research gap. It combines two types of data: 1) micro-level data from the China Family Panel Studies (CFPS) covering the years 2018, 2020, and 2022; and 2) macro-level metrics of regional digital economy development. The integrated dataset is used to examine the impact of digital economy development on SWB and identify its intrinsic mechanisms.ResultsDigital economy development significantly enhances residents’ SWB, with key transmission channels including the popularization of digital applications, improved information acquisition capabilities, and optimized digital living environments; meanwhile, heterogeneous regression analyses reveal that the positive impact of digital economy development on SWB varies significantly by age and frequency of digital technology usage, and mediation effect tests further confirm that the digital economy influences SWB primarily through five pathways, namely economic improvement, health enhancement, life quality upgrading, environmental optimization, and governance efficiency improvement.DiscussionStrengthening the construction of digital infrastructure, establishing tiered intervention mechanisms to address heterogeneous impacts across age and usage frequency groups, developing dynamic evaluation systems for digital economy welfare effects, and building a new digital governance paradigm that balances efficiency and fairness are targeted recommendations. These measures aim to fully leverage the welfare-enhancing role of the digital economy, ultimately promoting overall societal welfare and improving residents’ quality of life.